POLYMORPHISM AND POLYMORPH CHARACTERISATION IN PHARMACEUTICALS - Gosar, Dr Amit; Hussain, Dr Sayyed; Shaikh, Dr Tabrez (Journal of Biomedical and Pharmaceutical Research, 2019)
Polymorphism is the ability of a specific chemical compound to crystallize in more than one crystalline form. Polymorphs had a different arrangement of the molecule in the given crystal lattice and may properties such as packing properties, thermodynamic properties, spectroscopic properties, kinetic properties, surface properties and mechanical properties. Polymorph can be classified in various class such as crystalline, amorphous, hydrate and solvate. Polymorphs are categorized into two types, enantiotropes and monotropes, depending upon their stability with respect to the range of temperatures and pressures. There are various guidelines for the control of polymorphs in drug substances and drug product. Different analytical techniques are used for the detection, quantification and characterisation of the polymorphs in the drug substances and drug products. Control of polymorph in a drug substance and drug product is important for the safety and efficacy of the drug. Keywords: Polymorphism, classification, guidelines, characterisation, drug substances.